Event-triggered adaptive NN practical finite-time control with its application to MPCVD reactors. Issue 3 (February 2023) - Yu, Xinghu; Yang, Jiaxing; Meng, Xinbo; Zheng, Xiaolong; Yang, Xuebo
Abstract: The practical finite-time control problem of uncertain nonlinear systems is investigated in this paper. To address the uncertain nonlinearities of the system, neural networks are introduced to approximate the lumped nonlinearities containing the system unknown functions. On the other hand, to alleviate the signal transmission pressure of the system, an improved event-triggered mechanism is presented to reduce the controller update frequency without degrading the control performance of the system. By using practical finite-time stability, it is obtained that the system tracking errors are practical finite-time stable without Zeno behavior. Finally, the effectiveness of the proposed method is verified by the simulation results of its application to a microwave plasma chemical vapor deposition (MPCVD) reactor system.